2017
DOI: 10.1038/s41467-017-01343-4
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and phasing of structural variation in patient genomes using nanopore sequencing

Abstract: Despite improvements in genomics technology, the detection of structural variants (SVs) from short-read sequencing still poses challenges, particularly for complex variation. Here we analyse the genomes of two patients with congenital abnormalities using the MinION nanopore sequencer and a novel computational pipeline—NanoSV. We demonstrate that nanopore long reads are superior to short reads with regard to detection of de novo chromothripsis rearrangements. The long reads also enable efficient phasing of gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
236
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 336 publications
(240 citation statements)
references
References 53 publications
(86 reference statements)
3
236
0
1
Order By: Relevance
“…Notably, long reads are critical in structural variation analysis and the complete sequencing of repetitive DNA contents of clinical utility. Another group developed a new bioinformatics tool, NanoSV, for structural variation detection with nanopore data using split read mapping (Cretu Stancu et al, 2017). Another group developed a new bioinformatics tool, NanoSV, for structural variation detection with nanopore data using split read mapping (Cretu Stancu et al, 2017).…”
Section: Ultr A-long Re Ads -" Whale Watching"mentioning
confidence: 99%
See 4 more Smart Citations
“…Notably, long reads are critical in structural variation analysis and the complete sequencing of repetitive DNA contents of clinical utility. Another group developed a new bioinformatics tool, NanoSV, for structural variation detection with nanopore data using split read mapping (Cretu Stancu et al, 2017). Another group developed a new bioinformatics tool, NanoSV, for structural variation detection with nanopore data using split read mapping (Cretu Stancu et al, 2017).…”
Section: Ultr A-long Re Ads -" Whale Watching"mentioning
confidence: 99%
“…Norris and colleagues demonstrated that nanopore sequencers could detect large-scale structural variations, including large deletions, inversions, and translocations related to the inactivation of tumor suppressor genes in pancreatic cancer, with very few reads (Norris, Workman, Fan, Eshleman, & Timp, 2016). Another group developed a new bioinformatics tool, NanoSV, for structural variation detection with nanopore data using split read mapping (Cretu Stancu et al, 2017). Mitsuhashi and colleagues successfully identified a full-length microsatellite repeat spanning 49,877 bp in the D4Z4 array responsible for facioscapulohumeral muscular dystrophy .…”
Section: Ultr A-long Re Ads -" Whale Watching"mentioning
confidence: 99%
See 3 more Smart Citations